Preparation method and application of lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability
The lithium-rich manganese oxide positive electrode material is prepared through composite modification treatment of citric acid and oleic acid, which solves the problem of insufficient structural stability and electrochemical performance, and achieves high capacity and long cycle stability, which is suitable for the application of new energy vehicle batteries.
Patent Information
- Application Number
- CN202411968191.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing lithium-rich manganese oxide positive electrode materials face the problems of low efficiency, poor circulation performance and poor rate performance in practical applications, mainly due to their insufficient structural stability and poor interaction between the electrode and the electrolyte.
Li1.2Ni0.13Co0.13Mn0.54O2 was prepared by composite modification treatment of citric acid and oleic acid, thereby generating a spinel phase with high lithium ion conductance, which improved the structural stability and electrochemical properties of the material.
High capacity and long cycle stability are achieved, especially at high current density, excellent cycle performance and rate performance, reducing production costs and simplifying processes for large-scale commercial applications.
Smart Images

Figure CN119650680A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy vehicle battery electrode materials, and in particular to a preparation method and application of a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability. Background Art
[0002] With the rapid development of new energy technologies, lithium-ion batteries play a key role in electric vehicles. However, although the energy density of existing lithium-ion batteries is close to 300Wh / kg, it still cannot meet the growing demand for power batteries for new energy vehicles. As an important component of lithium-ion batteries, the positive electrode has an important impact on battery performance, cost-effectiveness, life and safety.
[0003] Lithium-rich manganese oxides, due to their unique anion and cation redox reactions, offer higher theoretical specific capacity and energy density, and are considered the most promising cathode materials for the next generation of lithium-ion batteries. However, in practical applications, lithium-rich manganese oxides face challenges such as low first coulombic efficiency, poor cycle performance, and poor rate performance, mainly due to the phase transition of lithium-rich manganese oxide electrode materials, the adverse interaction between lithium-rich manganese oxide electrodes and electrolytes, and the irreversible oxygen release of lithium-rich manganese-based cathode materials during charging and discharging. Therefore, improving the structural stability of lithium-rich manganese oxides has become the main research direction.
[0004] At present, improving the structural stability of lithium-rich manganese oxide mainly includes element doping and surface coating modification. CN118899424A discloses "a modified lithium-rich manganese-based positive electrode material and its preparation method and application", and prepares a lithium-rich manganese-based material doped with phosphorus and coated with rGO, including a core and a coating layer on the surface of the core. The lithium-rich manganese-based precursor can reduce the migration of transition metal ions and improve structural stability by doping with phosphorus and coating with rGO. It can also form oxygen vacancies in the material to prevent oxygen from escaping. At the same time, it also increases the transfer channel of electrons, improves the conductivity, and thus improves the capacity of the material. CN118684271A discloses "a modified lithium-rich manganese-based positive electrode material and its preparation method and application", and the hydroxide precursor material of the lithium-rich manganese-based positive electrode material is dispersed in an organic solvent, bismuth nitrate, tellurium dioxide and an organic ligand are added, and a hydrothermal reaction is carried out to obtain an intermediate product; after the intermediate product is mixed with a lithium source, it is sintered to obtain a coated and modified lithium-rich manganese-based positive electrode material. The coated modified lithium-rich manganese-based positive electrode material has good structural stability and rapid lithium ion deintercalation performance, which is manifested in the fact that the battery using this as the positive electrode material has a higher capacity retention rate. The above methods all reconstruct the lithium-rich manganese surface by introducing foreign atoms, which will cause surface segregation and make the surface reconstruction layer of the modified lithium-rich manganese oxide uneven, which will lead to unstable performance, cumbersome steps, high production costs, and disadvantages of large-scale commercial applications. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a preparation method and application of a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability. The lithium-rich manganese-based positive electrode material is modified by a composite of oleic acid and citric acid. The process is simple, and a spinel phase with high lithium ion conductivity is generated. It has a high specific capacity and excellent cycle performance at high current density.
[0006] The technical solution of the present invention is:
[0007] A method for preparing a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability, characterized in that: the lithium-rich manganese oxide positive electrode material Li is prepared by composite modification treatment of citric acid and oleic acid 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.
[0008] Further, the following steps are included:
[0009] (1) Preparation of precursor solution
[0010] Lithium acetate dihydrate, nickel acetate tetrahydrate, cobalt acetate tetrahydrate, manganese acetate tetrahydrate and citric acid monohydrate are mixed and added into deionized water, stirred evenly, and oleic acid is added to prepare a drive solution;
[0011] (2) Preparation of precursor materials
[0012] The precursor solution prepared in step (1) is spray-dried to obtain a precursor material;
[0013] (3) Preparation of positive electrode materials
[0014] The precursor material prepared in step (2) is heat-treated in an air atmosphere to obtain a lithium-rich manganese oxide positive electrode material Li with high capacity and long cycle stability. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.
[0015] Furthermore, in step (1), the molar ratio of lithium acetate dihydrate, nickel acetate tetrahydrate, cobalt acetate tetrahydrate and manganese acetate tetrahydrate is 0.1872:0.0195:0.0195:0.081.
[0016] Furthermore, the total concentration of metal acetate in the precursor solution in step (1) is 0.15 mol / L.
[0017] Furthermore, the stirring speed in step (1) is 500 rpm, the time is 1 h, and the temperature is room temperature.
[0018] Furthermore, the concentration of citric acid monohydrate in the precursor solution in step (1) is 0.4 mol / L, and the volume of oleic acid added accounts for 0.5-3% of the volume of deionized water in the precursor solution.
[0019] Furthermore, during spray drying in step (2), the inlet temperature of the spray drying is 200-250°C, the outlet temperature is 110-115°C, and the feed rate is 1-2L / h.
[0020] Further preferably, during the spray drying in step (2), the inlet temperature of the spray drying is 230° C., the outlet temperature is 115° C., and the feed rate is 1 L / h.
[0021] Furthermore, the heat treatment conditions in step (3) are: in an air atmosphere, heating to 1000° C. at a heating rate of 3° C. / min and keeping the temperature for 20 min.
[0022] An application of the lithium-rich manganese oxide positive electrode material prepared by the above preparation method in preparing a positive electrode for a lithium-ion battery.
[0023] The beneficial effects of the present invention are:
[0024] (1) The lithium-rich manganese material was compositely modified by adjusting the addition amount of citric acid monohydrate combined with oleic acid without introducing other foreign elements, which effectively reduced the particle size and increased the interplanar spacing; at the same time, a highly conductive and lithium-conductive spinel phase was generated, which significantly improved the mobility of lithium ions, allowing the material to exhibit excellent cycling performance and rate performance at high current density on the basis of high capacity.
[0025] (2) The lithium-ion batteries prepared using the modified material exhibit high capacity and excellent cycle stability at different current densities. For example, the capacity retention rate is as high as 94.98% after 500 cycles at a current density of 200 mA / g, and it also has a high capacity of 155.31 mAh / g at a current density of 1000 mA / g, and good cycle stability.
[0026] (3) The preparation method of the lithium-rich manganese-based positive electrode material provided has a simple synthesis process and low material cost, which is conducive to reducing production costs; the modification method is green and efficient, which is conducive to large-scale production and application.
[0027] In summary, this patent achieves a significant improvement in the electrochemical performance of lithium-rich manganese-based positive electrode materials through an innovative modification method of oleic acid and citric acid combined with a simple synthesis process. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 XRD diagrams of lithium-rich manganese oxide positive electrode materials obtained in Examples 1-2 and Comparative Example 1 of the present invention;
[0029] Figure 2 The SEM images of the lithium-rich manganese oxide positive electrode materials prepared in Examples 1-2 and Comparative Example 1 of the present invention;
[0030] Figure 3 XPS O1s graph of lithium-rich manganese oxide positive electrode materials obtained in Examples 1-2 and Comparative Example 1 of the present invention;
[0031] Figure 4 XPS Mn3s graph of lithium-rich manganese oxide positive electrode materials obtained in Examples 1-2 and Comparative Example 1 of the present invention;
[0032] Figure 5 The first charge and discharge diagram of the lithium-rich manganese oxide positive electrode material prepared in Examples 1-3 of the present invention and Comparative Example 1;
[0033] Figure 6 The first charge and discharge diagram of the lithium-rich manganese oxide positive electrode material obtained in Example 1 of the present invention and Comparative Examples 3-4;
[0034] Figure 7 This is the first charge and discharge diagram of the lithium-rich manganese oxide positive electrode material obtained in Comparative Examples 1 and 2 of the present invention;
[0035] Figure 8 The cycle performance of the lithium-rich manganese oxide positive electrode material obtained in Examples 1-2 of the present invention and Comparative Example 1 at a current density of 200 mA / g;
[0036] Fig. 9 The cycle performance of the lithium-rich manganese oxide positive electrode material obtained in Example 1 of the present invention and Comparative Examples 3-4 at a current density of 200 mA / g;
[0037] Fig.10 The cycle performance of the lithium-rich manganese oxide positive electrode material obtained in Comparative Examples 1 and 2 of the present invention at a current density of 200 mA / g;
[0038] Fig.11 The rate performance diagram of the lithium-rich manganese oxide positive electrode material obtained in Examples 1-2 of the present invention and Comparative Example 1;
[0039] Fig.12 The cycle performance of the lithium-rich manganese oxide positive electrode material prepared in Examples 1-2 of the present invention and Comparative Example 1 at a current density of 1000 mA / g. DETAILED DESCRIPTION
[0040] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] Example 1
[0042] (1) Preparation of precursor solution
[0043] Weigh 19.098 g of lithium acetate dihydrate (lithium acetate dihydrate is in excess of 4% wt to compensate for lithium loss during heat treatment), 4.852 g of nickel acetate tetrahydrate, 4.857 g of cobalt acetate tetrahydrate and 19.852 g of manganese acetate tetrahydrate, dissolve them in 1 L of deionized water, add 84.056 g of citric acid monohydrate and 5 mL of oleic acid, and mechanically stir at 500 rpm for 1 h at room temperature to obtain a precursor solution;
[0044] (2) Preparation of precursor materials
[0045] The precursor solution obtained in step (1) is sent to a spray dryer by a peristaltic pump, the inlet temperature of the spray dryer is set to 230° C., the outlet temperature is set to 115° C., and the feed rate is set to 1 L / h, and spray drying is performed to obtain a precursor material;
[0046] (3) Preparation of positive electrode materials
[0047] The precursor material obtained in step (2) is placed in an alumina crucible, wherein the alumina crucible has a length of 120 mm, a width of 120 mm, and a height of 50 mm. The alumina crucible is placed in a box furnace, and heated to 1000° C. at a heating rate of 3° C. / min in an air atmosphere, and heat treated at 1000° C. for 20 min to obtain a lithium-rich manganese oxide positive electrode material Li 200 wt % modified by oleic acid and citric acid. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, recorded as LRO / 0.4mol-0.5%.
[0048] Example 2
[0049] The preparation method is the same as that in Example 1, except that 30 mL of oleic acid is added when preparing the precursor solution. The obtained modified positive electrode material is recorded as LRO / 0.4 mol-3%.
[0050] (1) Preparation of precursor solution
[0051] Weigh 19.098 g of lithium acetate dihydrate (lithium acetate dihydrate is in excess of 4% wt to compensate for lithium loss during heat treatment), 4.852 g of nickel acetate tetrahydrate, 4.857 g of cobalt acetate tetrahydrate and 19.852 g of manganese acetate tetrahydrate, dissolve them in 1 L of deionized water, add 84.056 g of citric acid monohydrate and 30 mL of oleic acid, and mechanically stir at 500 rpm for 1 h at room temperature to obtain a precursor solution;
[0052] (2) Preparation of precursor materials
[0053] The precursor solution obtained in step (1) is sent to a spray dryer by a peristaltic pump, the inlet temperature of the spray dryer is set to 230° C., the outlet temperature is set to 115° C., and the feed rate is set to 1 L / h, and spray drying is performed to obtain a precursor material;
[0054] (3) Preparation of positive electrode materials
[0055] The precursor material obtained in step (2) is placed in an alumina crucible, wherein the alumina crucible has a length of 120 mm, a width of 120 mm, and a height of 50 mm. The alumina crucible is placed in a box furnace, and heated to 1000° C. at a heating rate of 3° C. / min in an air atmosphere, and heat treated at 1000° C. for 20 min to obtain a lithium-rich manganese oxide positive electrode material Li 200 wt % modified by oleic acid and citric acid. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.
[0056] Example 3
[0057] The preparation method is the same as that in Example 1, except that 10 mL of oleic acid is added when preparing the precursor solution. The obtained modified positive electrode material is recorded as LRO / 0.4 mol-1%.
[0058] (1) Preparation of precursor solution
[0059] Weigh 19.098 g of lithium acetate dihydrate (lithium acetate dihydrate is in excess of 4% wt to compensate for lithium loss during heat treatment), 4.852 g of nickel acetate tetrahydrate, 4.857 g of cobalt acetate tetrahydrate and 19.852 g of manganese acetate tetrahydrate, dissolve them in 1 L of deionized water, add 84.056 g of citric acid monohydrate and 10 mL of oleic acid, and mechanically stir at 500 rpm for 1 h at room temperature to obtain a precursor solution;
[0060] (2) Preparation of precursor materials
[0061] The precursor solution obtained in step (1) is sent to a spray dryer by a peristaltic pump, the inlet temperature of the spray dryer is set to 230° C., the outlet temperature is set to 115° C., and the feed rate is set to 1 L / h, and spray drying is performed to obtain a precursor material;
[0062] (3) Preparation of positive electrode materials
[0063] The precursor material obtained in step (2) is placed in an alumina crucible, wherein the alumina crucible has a length of 120 mm, a width of 120 mm, and a height of 50 mm. The alumina crucible is placed in a box furnace, and heated to 1000° C. at a heating rate of 3° C. / min in an air atmosphere, and heat treated at 1000° C. for 20 min to obtain a lithium-rich manganese oxide positive electrode material Li 200 wt % modified by oleic acid and citric acid. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.
[0064] Comparative Example 1: No oleic acid added
[0065] (1) Preparation of precursor solution
[0066] 19.098 g of lithium acetate dihydrate, 4.852 g of nickel acetate tetrahydrate, 4.857 g of cobalt acetate tetrahydrate and 19.852 g of manganese acetate tetrahydrate were weighed and dissolved in 1 L of deionized water, and 84.056 g of citric acid monohydrate was added, and lithium acetate dihydrate accounting for 4% of the mass fraction of lithium acetate dihydrate was additionally added to compensate for the lithium loss during the heat treatment; the mixture was mechanically stirred at 500 rpm for 1 h at room temperature to obtain a precursor solution.
[0067] (2) Preparation of precursor materials
[0068] The precursor solution obtained in step (1) is sent to a spray dryer by a peristaltic pump. The inlet temperature of the spray dryer is set to 230°C, the outlet temperature is set to 115°C, and the feed rate is set to 1L / h. The precursor material is obtained by spray drying under high temperature and high pressure.
[0069] (3) Preparation of positive electrode materials
[0070] The precursor material obtained in step (2) is placed in an alumina crucible, wherein the alumina crucible has a length of 120 mm, a width of 120 mm, and a height of 50 mm. The alumina crucible is placed in a box furnace, heated at a heating rate of 3°C / min in an air atmosphere, and heat treated at 1000°C for 20 min to obtain Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 positive electrode material, denoted as LRO / 0.4mol.
[0071] Comparative Example 2: No citric acid is added and the amount of citric acid monohydrate is increased
[0072] The difference between this comparative example and comparative example 1 is that the amount of citric acid monohydrate added in the preparation of the precursor solution is 126.084 g, and the other conditions are the same as those in comparative example 1. The obtained modified positive electrode material is recorded as LRO / 0.6 mol.
[0073] Comparative Example 3: Only increase the amount of oleic acid
[0074] The difference between this comparative example and Example 1 is that 40 ml of oleic acid is added when preparing the precursor solution. The other conditions are the same as Example 1. The obtained modified positive electrode material is recorded as LRO / 0.4 mol-4%.
[0075] Comparative Example 4: Only the amount of citric acid monohydrate is increased
[0076] The difference between this comparative example and comparative example 1 is that when preparing the precursor solution, the amount of citric acid monohydrate added is 126.084 g, the amount of oleic acid added is 5 mL, and the other conditions are the same as comparative example 1. The obtained modified positive electrode material is recorded as LRO / 0.6 mol-0.5%.
[0077] 1. XRD test of lithium-rich manganese-based positive electrode materials of Example 1, Example 2 and Comparative Example 1 of the present invention
[0078] XRD test was performed on the lithium-rich manganese-based positive electrode materials prepared in Example 1, Example 2 and Comparative Example 1 to test the basic structure of the lithium-rich manganese-based positive electrode materials. Figure 1 As shown. Figure 1 It can be seen that the prepared lithium-rich manganese oxides correspond to Li2MnO3 phase and LiMO2 phase, respectively, indicating that the target product was successfully synthesized. After composite modification with citric acid and oleic acid, the peak positions of (003) of LRO / 0.4mol-0.5% and LRO / 0.4mol-3% are shifted to the low angle direction, indicating that the interlayer spacing is increased. At the same time, the peak at (101), LRO / 0.4mol-0.5% and LRO / 0.4mol-3% both have spinel phase peaks, indicating that after composite modification, the surface of the lithium-rich manganese positive electrode material is coated with a spinel phase layer, which is beneficial to the transmission of lithium ions and greatly improves its rate and cycle performance.
[0079] II. SEM test of lithium-rich manganese-based positive electrode materials of Example 1, Example 2 and Comparative Example 1 of the present invention
[0080] The lithium-rich manganese-based positive electrode materials prepared in Example 1, Example 2 and Comparative Example 1 were subjected to SEM testing to test the surface morphology and size of the lithium-rich manganese-based positive electrode materials. Figure 2 As shown. Figure 2 It can be seen that the minimum particle size of LRO / 0.4mol-0.5% is 260nm, which means that a small amount of oleic acid added when the citric acid concentration is 0.4mol / L can reduce the particle size, which is particularly critical to the improvement of electrochemical performance.
[0081] III. XPS test of lithium-rich manganese-based positive electrode materials of Example 1, Example 2 and Comparative Example 1 of the present invention
[0082] XPS test was performed on the lithium-rich manganese-based positive electrode materials prepared in Example 1, Example 2 and Comparative Example 1 to test the surface structure of the lithium-rich manganese-based positive electrode materials. Figure 3 , Figure 4 As shown. Figure 3 , Figure 4 It can be seen that the oxygen vacancy content of the lithium-rich manganese-based positive electrode materials prepared in the embodiments of the present invention has increased, and the increase in LRO / 0.4mol-0.5% is more significant at 32.19%. The increase in oxygen vacancies helps to stabilize the lattice oxygen on the surface of the material. After calculation, the average valence of Mn is LRO / 0.4mol (+3.776), LRO / 0.4mol-0.5% (+4.012), and LRO / 0.4mol-3% (+3.832). The increase in the valence of Mn plays a role in stabilizing the structure. Among them, the valence of LRO / 0.4mol-0.5% reaches +4, combined with the spinel phase appearing in the (101) peak in XRD, it is speculated that Li4Mn5O 12 The high lithium ion conductivity spinel phase improves the capacity and cycle performance.
[0083] III. Electrochemical Performance Test of Lithium-Rich Manganese-Based Positive Electrode Materials of Example 1, Example 2 and Comparative Examples 1 to 4 of the Present Invention
[0084] (1) Preparation of positive electrode sheet
[0085] The lithium-rich manganese-based positive electrode materials and Super P prepared in Example 1, Example 2 and Comparative Examples 1-4 were weighed in a mass ratio of 8:1 and placed in a ball mill, tungsten carbide ball milling beads were added, the ball-to-material mass ratio in the ball mill was 100:1, and alcohol was added as a dispersant. After ball milling for 6 hours, the mixture was dried in a drying oven to obtain a mixture A;
[0086] Weigh 285 mg of mixture A and 1250 mg of 1.2% CMC solution, stir at room temperature for 2 h, ultrasonicate for 2 h, stir again for 2 h, coat on aluminum foil with a 0.15 μm scraper, dry in a vacuum drying oven at 110 ° C for 20 h, cut into electrodes with a diameter of 10 mm, and then transfer the cut electrodes to a vacuum oven at 115 ° C for 10 h for use.
[0087] (2) Assemble CR2025 stainless steel button battery
[0088] Using a metal lithium sheet as the negative electrode, 250 μL of LBC-3045I(G) commercial electrolyte was dripped into the battery. The CR2025 stainless steel button cell was assembled in a glove box filled with argon gas and with a moisture content of less than 0.01 ppm. The charge and discharge performance was tested after standing at 45°C for 40 hours.
[0089] (3) Electrochemical performance test of CR2025 stainless steel button battery
[0090] The cycle performance of the batteries prepared in Example 1, Example 2 and Comparative Examples 1-4 was tested by constant current charge and discharge. The test temperature was 25°C, the voltage window was 2.0-4.8V, and the current densities tested were 0.1C, 0.2C, 0.5C, 1C, 2C, 5C and 10C, respectively, where 1C = 200mA / g.
[0091] like Figure 5-7 As shown, the lithium-ion battery prepared by the lithium-rich manganese oxide positive electrode material LRO / 0.4mol-0.5% in the present invention has a maximum first discharge specific capacity of 303.90mAh / g at a current density of 20mA / g. The first discharge specific capacities of LRO / 0.4mol-3%, LRO / 0.4mol-4%, LRO / 0.6mol-0.5%, LRO / 0.4mol, and LRO / 0.6mol are 274.13, 231.58, 269.97, 262.41, and 256.11mAh / g, respectively, indicating that adding excessive oleic acid and increasing the concentration of citric acid will reduce the specific capacity.
[0092] like Figure 8-11 As shown, the lithium-ion battery prepared by the lithium-rich manganese oxide positive electrode material LRO / 0.4mol-0.5% in the present invention has a capacity retention rate of up to 94.98% after 500 cycles at a current density of 200mA / g. After 500 cycles at a current density of 200mA / g, the capacity retention rates of LRO / 0.4mol-4%, LRO / 0.6mol-0.5%, LRO / 0.4mol, and LRO / 0.6mol are 75.02%, 71.62%, 83.79%, and 62.13%, respectively. This is mainly because the increase in interlayer spacing and the formation of spinel phases lead to rapid lithium ion transmission, and the increase in oxygen vacancy content regulates the surface electronic structure of the modified lithium-rich manganese positive electrode material, so that the Mn valence state is increased, the disproportionation reaction is reduced, the transition metal is prevented from dissolving the material structure, and the cycle stability is improved. The lithium-ion battery prepared by the lithium-rich manganese oxide positive electrode material LRO / 0.4mol-0.5% in the present invention maintains excellent rate performance in the rate performance tests of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C and 10C.
[0093] like Fig.12As shown, due to the increase of surface oxygen vacancy defects after the composite treatment of citric acid and oleic acid, the electrostatic effect will increase the interlayer spacing and generate a spinel phase structure with high lithium ion conductivity, so that the lithium-rich manganese oxide positive electrode material prepared by LRO / 0.4mol-0.5% and LRO / 0.4mol-3% in the present invention still provides 155.31mAh / g and 135.75mAh / g capacity (the capacity of LRO / 0.4mol is 123.65mAh / g) at a current density of 1000mA / g. After 500 cycles, the capacity retention rate of the lithium-ion battery assembled with the LRO / 0.4mol-0.5% sample is as high as 77.35%, showing excellent rate performance.
[0094] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability, characterized in that: Lithium-rich manganese oxide cathode material Li prepared by composite modification of citric acid and oleic acid 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.
2. The method for preparing a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability according to claim 1, characterized in that: The following steps are involved: (1) Preparation of precursor solution Lithium acetate dihydrate, nickel acetate tetrahydrate, cobalt acetate tetrahydrate, manganese acetate tetrahydrate and citric acid monohydrate are mixed and added into deionized water, stirred evenly, and oleic acid is added to prepare a drive solution; (2) Preparation of precursor materials The precursor solution prepared in step (1) is spray-dried to obtain a precursor material; (3) Preparation of positive electrode materials The precursor material prepared in step (2) is heat-treated in an air atmosphere to obtain a lithium-rich manganese oxide positive electrode material Li with high capacity and long cycle stability. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.
3. The method for preparing a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability according to claim 2, characterized in that: In the step (1), the molar ratio of lithium acetate dihydrate, nickel acetate tetrahydrate, cobalt acetate tetrahydrate and manganese acetate tetrahydrate is 0.1872:0.0195:0.0195:0.
081.
4. The method for preparing a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability according to claim 2, characterized in that: The total concentration of metal acetate in the precursor solution in step (1) is 0.15 mol / L.
5. The method for preparing a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability according to claim 2, characterized in that: The stirring speed in step (1) is 500 rpm, the time is 1 h, and the temperature is room temperature.
6. The method for preparing a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability according to claim 2, characterized in that: The concentration of citric acid monohydrate in the precursor solution in step (1) is 0.4 mol / L, and the volume of oleic acid added accounts for 0.5-3% of the volume of deionized water in the precursor solution.
7. The method for preparing a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability according to claim 2, characterized in that: During spray drying in step (2), the inlet temperature of the spray drying is 200-250° C., the outlet temperature is 110-115° C., and the feed rate is 1-2 L / h.
8. The method for preparing a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability according to claim 7, characterized in that: During spray drying in step (2), the inlet temperature of the spray drying is 230° C., the outlet temperature is 115° C., and the feed rate is 1 L / h.
9. The method for preparing a lithium-rich manganese oxide positive electrode material with high capacity and long cycle stability according to claim 2, characterized in that: The heat treatment conditions in step (3) are: in an air atmosphere, heating to 1000° C. at a heating rate of 3° C. / min and keeping the temperature for 20 minutes.
10. Use of the lithium-rich manganese oxide positive electrode material prepared by the preparation method as claimed in claim 1 in preparing a positive electrode for a lithium-ion battery.
Citation Information
Patent Citations
Lithium ion battery cathode material rich in lithium and manganese and preparation method thereof
CN104810519A
Lithium ion battery lithium-rich manganese-based positive electrode material and spray drying preparation method thereof
CN108878862A
Lithium-rich ternary anode material and environment-friendly preparation method thereof
CN109768272A
Lithium-rich manganese-based positive electrode material and preparation method thereof
CN116598470A
Positive electrode active material, and lithium battery containing positive electrode active material
JP2015022958A
Cited By
Lithium-rich manganese-based positive electrode material and preparation method and application thereof
CN120565647A